The Effect of Physical Exercise on Depression in Menopausal Women - Fitriana, Lisna Anisa; Nasution, Lina Anisa; Darmawati, Irma; Setyarini, Elizabeth Ari (Universitas Pendidikan Indonesia, 2021)
Mood disorders are a frequent complaint experienced by women during menopause due to hormonal changes. Physical exercise is known to reduce depression, but research on menopausal women is limited. The purpose of this study was to determine the effect of physical exercise on depression in menopausal women. The study design used was quasi-experimental with pre-test and post-test for 16 weeks. The measuring instrument used was a GDS (Geriatric Depression Scale). The research subjects consisted of 34 menopausal women aged 45-65 years. Subjects were divided into two groups, including the physical exercise group (2x90 minutes/week, n=17) and the control group (n=17). The results showed that physical exercise significantly decreased depression (p=0.013) in the physical exercise group compared to the control group. It concludes that regular exercise is effective for preventing and treating mood disorders that occur when menopause.